Impacts of climate change on shrimp farming in the South-West coastal region of Bangladesh (Research in Agriculture Livestock and Fisheries, 2016)
The inhabitants of south west region of Bangladesh are prone to floods, cyclones, salinity intrusion and droughts, and the incidence of these hazards is rising. Recently two cyclones (known as Aila and Sidr) hit the southwest region of Bangladesh. Considering the above in view, research had been conducted for understanding the impacts and adaptation measures through sustainable coastal resources management in the cyclone affected greater Khulna areas. The present study was carried out (from January to June, 2011) to understand impacts of climate change on the shrimp farming, hatchery and nursery operations in the selected upazilas (Paikgacha and Shyamnagar). The study was conducted both primary and secondary data sources. To collect primary data different methods had been adopted which were informal interview, a pre-formulated questionnaire survey and Focused Group Discussion (FGD). In the study areas, about 80-90% people are involved with shrimp farming with 10-15 years experience. About 60% shrimp farmers thought that the weather has changed abruptly within the last 5 years. The study showed that the first and foremost factor is high temperature (49.5%). Majority (43.21%) encountered that temperature hampered the farm operation while lower growth (54%), low production (19%), loss of crops (13%), less water (4%), mortality (4%), and diseases (4%) occurred due to less rainfall or no rain. From the study, farmers (80%) reported susceptibility of shrimp to diseases in body deformation, spots or lesions on skins while 13.33% mentioned fry susceptibility to diseases. Some time oriented and need based adaptations in shrimp farming are now most concern. Government and other stakeholders should come forward to execute research for adaptations.Res. Agric., Livest. Fish.3(1): 227-239, April 2016